2014
DOI: 10.1593/tlo.13811
|View full text |Cite|
|
Sign up to set email alerts
|

Errors in Quantitative Image Analysis due to Platform-Dependent Image Scaling

Abstract: Corrective actions for image scaling are suggested for manufacturers and quantitative imaging community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 17 publications
0
44
0
Order By: Relevance
“…The slope of the line that describes this relationship in each voxel represents the ADC. Despite using different scanner-specific techniques and image scaling methods to compute ADC maps, it was demonstrated that ADC measurements provided by different vendors were within 3% of the true value [18] using the diffusion coefficient of water at 0 ℃ as a reference.…”
Section: Sb/s0mentioning
confidence: 99%
“…The slope of the line that describes this relationship in each voxel represents the ADC. Despite using different scanner-specific techniques and image scaling methods to compute ADC maps, it was demonstrated that ADC measurements provided by different vendors were within 3% of the true value [18] using the diffusion coefficient of water at 0 ℃ as a reference.…”
Section: Sb/s0mentioning
confidence: 99%
“…Despite the use of standardized imaging protocol and parameters, variability related to different MR imaging gradient systems and calibrations, software packages, and image scaling remains a major source of errors in quantitative image analysis such as ours. 19 We also showed that ADC 10 was predictive of LGG progression, whereas ADC mean was not. In contrast to mean values that can be diluted by tissue and microenviromental heterogeneity, the lowest 10th percentile value was chosen to represent regions of tumor with the highest cellular density and proliferation.…”
Section: Discussionmentioning
confidence: 56%
“…Quantification of contrast enhancement can be obtained using the relative contrast enhancement (RCE) feature, which is incorporated in the Magnetic Resonance Index of Activity (MaRIA) [6]. However, manual region of interest placement and corrections of signal intensity values on certain scanner types complicate the use of these measurements [30].…”
Section: Discussionmentioning
confidence: 99%